How does experience impact on domestic tourist’s satisfaction? testing the mediating role of service quality - Rahman, Muhammad Sabbir; Madi Bin, Abdullah (Associated Management Consultants (P) Ltd ., 2014)
The aim of this paper is to explore the impact of tourist’s experience to the tourist’s satisfaction and examine the mediating effect of service quality in this relationship, for Bangladeshi domestic tourists. The study utilised a review of the literature to propose a conceptual model that posits that: Tourists’ experience is positively related to their overall satisfaction when service quality mediates the relationship. The model is examined in an empirical study with data from a survey among 280 domestic tourists by utilising the convenience sampling procedure from selected tourist destination in Bangladesh. The constructs were then analysed by using exploratory factor analysis, and validation through the use of confirmatory factor analysis and structural equation modelling. The findings of the study suggest that experience plays a significant role in tourists’ satisfaction, while service quality plays a strong mediating role. The findings from this research provide a meaningful source of information about domestic tourists’ experience and their expectation from the service providers. The findings also provide broad guidelines for improving the quality of tourism services in a totally manner in the Bangladesh tourism sector. This paper demonstrates how service quality mediates the relationship between tourists’ experience and tourist’s satisfaction. To the best of researchers’ knowledge, this is the first ever and only research so far on Bangladeshi domestic tourists’ perception in testing their experience and satisfaction by considering service quality as a mediating role.